2015
DOI: 10.3892/ijmm.2015.2404
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol alleviates the cytotoxicity induced by the radiocontrast agent, ioxitalamate, by reducing the production of reactive oxygen species in HK-2 human renal proximal tubule epithelial cells in vitro

Abstract: Radiocontrast-induced nephropathy (RIN) is one of the leading causes of hospital-acquired acute kidney injury (AKI). The clinical strategies currently available for the prevention of RIN are insufficient. In this study, we aimed to determine whether resveratrol, a polyphenol phytoalexin, can be used to prevent RIN. For this purpose, in vitro experiments were performed using a human renal proximal tubule epithelial cell line (HK-2 cells). Following treatment for 48 h, the highly toxic radiocontrast agent, ioxit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 53 publications
1
31
0
1
Order By: Relevance
“…In agreement with our results, it has been reported that SIRT-1 levels are decreased in diabetic patients, as well as in highglucose-treated renal tubular cells (Hao & Haase, 2010;Hou et al, 2014); indeed the therapeutic use of sirtuins is currently in clinical trials, as they are likely to improve the diabetic condition in humans (Hao & Haase, 2010). In the present work, EC and DHPAA alone increased SIRT-1 levels in NRK-52E cells, in agreement with other studies performed with other flavonoids such as puerarin, and with the stilbene resveratrol in renal cultured cells, and cocoa and EC in adipose tissue of rats (Huang et al, 2016;X. Li et al, 2017;Rabadan-Chávez, Quevedo-Corona, Miliar-Garcia, Reyes-Maldonado, & Jaramillo-Flores, 2016).…”
Section: Discussionsupporting
confidence: 91%
“…In agreement with our results, it has been reported that SIRT-1 levels are decreased in diabetic patients, as well as in highglucose-treated renal tubular cells (Hao & Haase, 2010;Hou et al, 2014); indeed the therapeutic use of sirtuins is currently in clinical trials, as they are likely to improve the diabetic condition in humans (Hao & Haase, 2010). In the present work, EC and DHPAA alone increased SIRT-1 levels in NRK-52E cells, in agreement with other studies performed with other flavonoids such as puerarin, and with the stilbene resveratrol in renal cultured cells, and cocoa and EC in adipose tissue of rats (Huang et al, 2016;X. Li et al, 2017;Rabadan-Chávez, Quevedo-Corona, Miliar-Garcia, Reyes-Maldonado, & Jaramillo-Flores, 2016).…”
Section: Discussionsupporting
confidence: 91%
“…Resveratrol was reported to exert cytoprotective effects through anti-inflammatory, anti-apoptotic and anti-oxidant actions via inducing the activation of sirtuin 1 (36). Resveratrol also alleviates the production of reactive oxygen species (37). These may be the main mechanisms of the protective function of resveratrol in alleviating sepsis-induced AKI.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, despite the inherent challenges encountered in the past years, there is need for a continued effort towards achieving optimal therapeutic interventions [Okusa et al 2016]. In this regard, the model of AKI that is most susceptible to pharmacological modulation is that due to pro-oxidative inflammation as in contrast-induced nephropathy [Huang et al 2016]. In view of a similar pathophysiology, in the face of vancomycin cytotoxicity, renal perfusion must be maintained by ensuring there is adequate intravenous hydration.…”
Section: Therapeutic Strategy For Vancomycininduced Akimentioning
confidence: 99%
“…However, in at least one study, there was a benefit from the use of iron-chelating antioxidant, 2,3-dihydroxybenzoic acid but there was no protection from 4-hydroxyl-2,2,6,6-tetramethylpiperidine-1-oxyl (Tempol; Sigma-Aldrich Co. LLC; 3050 Spruce St., St. Louis MO 63178), a superoxide dismutase mimetic compound [Naghibi et al 2007]. These therapeutic agents enhance the survival of renal tubular cells by reducing DNA fragmentation, apoptosis and necrosis; and in certain instances by the modulation of autophagy [Huang et al 2016]. Nevertheless, in contrast to the effect of cilastatin previously discussed, it is unclear if antioxidative strategy would place a limitation on the bactericidal activity of vancomycin [Humanes et al 2015].…”
Section: Antioxidative Therapymentioning
confidence: 99%